2021
DOI: 10.1038/s41598-021-87156-4
|View full text |Cite
|
Sign up to set email alerts
|

Electron guiding in macroscopic borosilicate capillaries with large bending angles

Abstract: This work presents experiments about the transmission of electrons with an energy of around 15 keV with beam currents up to 20 µA through macroscopic glass capillaries. A systematic study was conducted to experimentally investigate the transmission of electrons through borosilicate glass capillaries with curve angles of 90°, 180°, 270° and 360° for the first time. The focus of the work was to identify the conditions under which the injected electron current is transmitted through the capillary. It was also sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Additionally, it has been demonstrated that dielectric capillaries can transmit ion beams without any change in both the ion kinetic energy and the ion charge [66]. Capillary guiding peculiarities have been also studied for electron beams, revealing similar elastic and inelastic features of scattering by the inner capillary surface, while a time evolution of transmitted intensity for electrons remains essentially different from that of ions [67][68][69][70][71][72][73][74][75][76][77].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been demonstrated that dielectric capillaries can transmit ion beams without any change in both the ion kinetic energy and the ion charge [66]. Capillary guiding peculiarities have been also studied for electron beams, revealing similar elastic and inelastic features of scattering by the inner capillary surface, while a time evolution of transmitted intensity for electrons remains essentially different from that of ions [67][68][69][70][71][72][73][74][75][76][77].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of controlling electron beams with an energy up to 10 keV by dielectric channels have been actively investigated since 2007 [1,2]. At present, there is a large amount of experimental data on investigating the grazing interaction of electrons with an energy up to 20 keV with dielectric surfaces [3][4][5][6][7][8][9][10]. However, to date, there is no unambiguous answer to the question of the mechanism of such an interaction: whether the control effect is a consequence of the scattering of electrons at surface atoms, or whether self-consistent dynamic charge distribution on the surface of the dielectric sample acts as a determining factor as in the case of ions [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…绝缘微管造价低廉、体积小, 并且带电粒子在其中通过自组织调节的充电过程 传输而不需要额外的供能设备. 因此, 除正离子外, 负离子 [17][18][19][20] 、电子 [21][22][23][24][25][26][27][28][29][30][31][32] 、正电子 [33,34] 、μ子 [35,36] 等 各种不同性质的带电粒子在绝缘微管中输运机制 的研究也被广泛开展.…”
unclassified